ANALISIS PENERAPAN METODE MAISURA DALAM PEMBELAJARAN BACA AL-QUR’AN GUNA MENINGKATKAN KUALITAS BACAAN PADA USIA 7-11 TAHUN - Lailatul Ahadiyah; Budi Haryanto (Qolamuna : Jurnal Studi Islam, 2026)
Teaching children aged 7–11 years to read the Qur'an (BQ) requires methods that are appropriate to the cognitive development characteristics and reading abilities of the students. One of the methods used in tahsin and tahfidz learning is the Maisura Method, which emphasizes the accuracy of makhraj, the application of tajwid rules, and consistency of reading through structured learning stages. This study aims to analyze the application of the Maisura Method in BQ learning at MI Tarbiyatus Syarifah and to examine the differences in its application based on grade level, student ability groups, and pedagogical challenges faced by teachers. This study uses a descriptivequalitative approach with data collection techniques in the form of observations and interviews with BQ teachers and students aged 7–11 years. Data analysis was conducted using the Miles, Huberman, and Saldaña model through the stages of data condensation, data presentation, and conclusion drawing, and its validity was tested through triangulation. The results showed that the Maisura Method was applied systematically through the stages of providing reading examples, imitation, repetition, submission, and continuous correction. The effectiveness of this method varied across grade levels, with lower grade students showing a higher level of acceptance than higher grade students who already had existing reading patterns. Teacher accuracy and consistency were the main determinants of the success of this method in teaching reading. Keywords : The Maisura Method, Reading the Qur'an, Quality of Reading